Pentagon Problem

Geometry Level 2

In regular pentagon A B C D E , ABCDE, point M M is the midpoint of side A E . AE.

If line segments A C AC and B M BM intersect at point Z Z and Z A = 3 , ZA=3, what is the length of A B ? AB?

3 5 3\sqrt{5} 2 5 2 \sqrt{5} 4 4 3 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ayush G Rai
Nov 14, 2016

Let P P be the intersection of C E CE and B M BM . Let A B = x |AB|=x and denote φ = 1 + 5 2 \varphi=\dfrac{1+\sqrt{5}}{2} .

Claim: C E = φ × x |CE|=\varphi \times x .
Proof: We will apply Ptolemy's Theorem:
Inscribe a regular pentagon A B C D E ABCDE inside a circle. WLOG, let its side length be 1 1 . If we let the length of the diagonal be x x , then using Ptolemy's Theorem on ABCD tells us that x 2 = x + 1 x^{2}=x+1 . Using the quadratic formula and taking the positive root tells us that x = 1 + 5 2 = ϕ x=\dfrac{1+\sqrt{5}}{2} = \phi . Therefore, the length of the diagonal is ϕ \phi multiplied by the side length.

Note that A M B E M P \triangle AMB\cong\triangle EMP by A S A , ASA, hence E P = A B = x |EP|=|AB|=x .

Now note that B Z A P Z C \triangle BZA\sim\triangle PZC by A A A AAA and A B = x |AB|=x while C P = C E + E P = ( 1 + φ ) ( x ) |CP|=|CE|+|EP|=(1+\varphi)(x) .

It follows that C Z = ( 1 + φ ) A Z = 3 + 3 φ |CZ|=(1+\varphi)|AZ|=3+3\varphi . Hence A C = 6 + 3 φ |AC|=6+3\varphi and A B = A C φ = 6 + 3 φ φ = 3 5 |AB|=\dfrac{|AC|}{\varphi}=\dfrac{6+3\varphi}{\varphi}=\boxed{3\sqrt{5}} .

Very nice construction of P P . What motivated that?

Calvin Lin Staff - 4 years, 7 months ago

Log in to reply

I could see that AB and Ce were parallel and hence went to extend for similarity.

Ayush G Rai - 4 years, 7 months ago
Chew-Seong Cheong
Nov 14, 2016

Let the side length of the regular pentagon A B C D E ABCDE be a a . By sine rule , we have:

sin A B M A M = sin A M B A B sin A B M a 2 = sin ( 18 0 E A B A B M ) a Let A B M = θ 2 sin θ = sin ( 18 0 10 8 θ ) 2 sin θ = sin ( 7 2 θ ) 2 sin θ = sin 7 2 cos θ sin θ cos 7 2 tan θ = sin 7 2 2 + cos 7 2 \begin{aligned} \frac {\sin \angle ABM}{AM} & = \frac {\sin \angle AMB}{AB} \\ \frac {\sin {\color{#3D99F6}\angle ABM}}{\frac a2} & = \frac {\sin (180^\circ - \angle EAB - {\color{#3D99F6}\angle ABM})}a & \small {\color{#3D99F6} \text{Let }\angle ABM = \theta} \\ 2 \sin {\color{#3D99F6}\theta} & = \sin (180^\circ - 108^\circ - {\color{#3D99F6}\theta}) \\ 2 \sin \theta & = \sin (72^\circ - \theta) \\ 2 \sin \theta & = \sin 72^\circ \cos \theta - \sin \theta \cos 72^\circ \\ \tan \theta & = \frac {\sin 72^\circ}{2+\cos 72^\circ} \end{aligned}

By sine rule again,

sin A B M A Z = sin A Z B A B sin θ 3 = sin ( 18 0 3 6 θ ) a a sin θ = 3 sin ( 3 6 + θ ) a sin θ = 3 sin 3 6 cos θ + 3 sin θ cos 3 6 tan θ = 3 sin 3 6 a 3 cos 3 6 \begin{aligned} \frac {\sin \angle ABM}{AZ} & = \frac {\sin \angle AZB}{AB} \\ \frac {\sin \theta}3 & = \frac {\sin (180^\circ - 36^\circ - \theta)}a \\ a \sin \theta & = 3 \sin (36^\circ + \theta) \\ a \sin \theta & = 3 \sin 36^\circ \cos \theta +3 \sin \theta \cos 36^\circ \\ \tan \theta & = \frac {3 \sin 36^\circ}{a-3\cos 36^\circ} \end{aligned}

Therefore,

3 sin 3 6 a 3 cos 3 6 = sin 7 2 2 + cos 7 2 a 3 cos 3 6 3 sin 3 6 = 2 + cos 7 2 sin 7 2 a 3 cos 3 6 3 = 2 + 2 cos 2 3 6 1 2 cos 3 6 a = 3 + 6 cos 2 3 6 2 cos 3 6 + 3 cos 3 6 = 3 2 cos 3 6 + 6 cos 3 6 See Note. = 3 2 ( 1 + 5 4 ) + 6 ( 1 + 5 4 ) = 3 2 ( 4 1 + 5 + 1 + 5 ) = 3 5 \begin{aligned} \implies \frac {3 \sin 36^\circ}{a-3\cos 36^\circ} & = \frac {\sin 72^\circ}{2+\cos 72^\circ} \\ \frac {a-3\cos 36^\circ}{3 \sin 36^\circ} & = \frac {2+\cos 72^\circ}{\sin 72^\circ} \\ \frac {a-3\cos 36^\circ}3 & = \frac {2+ 2\cos^2 36^\circ-1}{2\cos 36^\circ} \\ \implies a & = \frac {3+ 6\cos^2 36^\circ}{2\cos 36^\circ} + 3\cos 36^\circ \\ & = \frac 3{2\color{#3D99F6}\cos 36^\circ} + 6\color{#3D99F6}\cos 36^\circ \quad \quad \small \text{See Note.} \\ & = \frac 3{2\color{#3D99F6}\left(\frac {1+\sqrt 5}4\right)} + 6\color{#3D99F6}\left(\frac {1+\sqrt 5}4\right) \\ & = \frac 32 \left(\frac 4{1+\sqrt 5} + 1+\sqrt 5 \right) \\ & = \boxed{3\sqrt 5} \end{aligned}


Note: Using the identity below:

cos π 5 + cos 3 π 5 = 1 2 2 cos π 5 + 2 cos 3 π 5 = 1 2 cos π 5 2 cos 2 π 5 = 1 2 cos π 5 4 cos 2 π 5 + 2 = 1 4 cos 2 π 5 2 cos π 5 1 = 0 cos π 5 = 1 + 5 4 \begin{aligned} \cos \frac \pi 5 + \cos \frac {3\pi}5 & = \frac 12 \\ 2\cos \frac \pi 5 + 2\cos \frac {3\pi}5 & = 1 \\ 2\cos \frac \pi 5 - 2\cos \frac {2\pi}5 & = 1 \\ 2\cos \frac \pi 5 - 4\cos^2 \frac \pi 5 + 2 & = 1 \\ 4\cos^2 \frac \pi 5 - 2\cos \frac \pi 5 - 1 & = 0 \\ \implies \cos \frac \pi 5 & = \frac {1+\sqrt 5}4 \end{aligned}

Nice way of incorporating the approach of calculating cos 3 6 \cos 36^ \circ using the pentagon.

Calvin Lin Staff - 4 years, 7 months ago

Let [ X Y Z ] [XYZ] be the area of triangle X Y Z \triangle XYZ . We have Z A B = 3 6 \angle ZAB=36^\circ , M A Z = 7 2 \angle MAZ=72^\circ and [ A B M ] = [ A B Z ] + [ A Z M ] [ABM]=[ABZ]+[AZM] . Let A B = x AB=x , then: x x 2 sin 10 8 2 = 3 x sin 3 6 2 + 3 x 2 sin 7 2 2 \dfrac{x \cdot \frac{x}{2}\sin 108^\circ}{2}=\dfrac{3x \sin 36^\circ}{2}+\dfrac{3\cdot \frac{x}{2} \sin 72^\circ}{2} Solve for x x , using the identity sin 10 8 = sin 7 2 \sin 108^\circ=\sin 72^\circ : x = 3 ( 2 sin 3 6 + sin 7 2 sin 7 2 ) x = 3 ( 2 sin 3 6 2 sin 3 6 cos 3 6 + 1 ) x = 3 ( 1 cos 3 6 + 1 ) x = 3 ( 5 1 + 1 ) x = 3 5 x=3\left(\dfrac{2\sin 36^\circ+\sin 72^\circ}{\sin 72^\circ}\right)\\ x=3\left(\dfrac{2\sin 36^\circ}{2\sin 36^\circ \cos 36^\circ}+1\right)\\ x=3\left(\dfrac{1}{\cos 36^\circ}+1\right)\\ x=3\left(\sqrt{5}-1+1\right)\\ x=\boxed{3\sqrt{5}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...